Immunomodulatory Effects of Tigecycline in Balb/C Mice - Elhayek Shada Y.; Fararjeh Mohammad A.; Assaf Areej M.; Abu-Rish Eman Y.; Bustanji Yasser (Acta Pharmaceutica)
Tigecycline is a glycylcycline antibiotic approved by the FDA for the treatment of complicated infections. Despite its effectiveness, the FDA announced a warning of increasing mortality associated with its use. There is, however, no clear explanation for this side effect. Previous reports found a possible effect of tigecycline on leukocyte proliferation and proinflammatory cytokine release. We t herefore i nvestigated the effect of tigecycline on the immune components and response in Balb/c mice in vivo and in vitro. It was found that tigecycline enhanced lymphocyte proliferation and significantly increased cellular infiltration within the footpad, as based on DTH testing, but reduced the hemagglutination titer. In splenocyte cultures, tigecycline suppressed splenocyte proliferation with IC50 3-5 mmol L-1, significantly increased IL-2 secretion and reduced IL-17 secretion in a dose dependent mode. In conclusion, tigecycline is safe at therapeutic and sub-therapeutic doses, but it could still have an immunomodulatory effect at higher doses. Use of higher doses of tigecycline requires further investigation.